2022
DOI: 10.1002/glia.24304
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring regional astrocyte diversity by cell type‐specific proteomic labeling in vivo

Abstract: Astrocytes exhibit regional heterogeneity in morphology, function and molecular composition to support and modulate neuronal function and signaling in a regionspecific manner. To characterize regional heterogeneity of astrocytic proteomes of different brain regions we established an inducible Aldh1l1-methionyl-tRNAsynthetase L274G (MetRS L274G ) mouse line that allows astrocyte-specific metabolic labeling of newly synthesized proteins by azidonorleucine (ANL) in vivo and subsequent isolation of tagged proteins… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 98 publications
(180 reference statements)
0
1
0
Order By: Relevance
“…Here, we use a nascent proteomic labeling system, MetRS L274G in the presence of ANL, to explore the proteomic contributions in the cross-talk between GBM and NPCs. Although this system has been used in other areas of neuroscience (62)(63)(64), cancer biology (65), and stem cell biology (66)(67)(68), neurogenesis and brain tumor cell-specific nascent proteomics has been relatively unexplored. Our approach to this system can now be used to profile GBM proteomic dynamics in vivo and can be more widely applied to other diseases and microenvironmental niches.…”
Section: Discussionmentioning
confidence: 99%
“…Here, we use a nascent proteomic labeling system, MetRS L274G in the presence of ANL, to explore the proteomic contributions in the cross-talk between GBM and NPCs. Although this system has been used in other areas of neuroscience (62)(63)(64), cancer biology (65), and stem cell biology (66)(67)(68), neurogenesis and brain tumor cell-specific nascent proteomics has been relatively unexplored. Our approach to this system can now be used to profile GBM proteomic dynamics in vivo and can be more widely applied to other diseases and microenvironmental niches.…”
Section: Discussionmentioning
confidence: 99%
“…This finding suggested that cerebellar astrocytes are more vulnerable to frataxin depletion than astrocytes from other brain regions. This specific cerebellar vulnerability could be partially attributed to the unique proteomic profile of astrocytes from the cerebellum, which differ from that of astrocytes in all other brain regions analyzed (Prabhakar et al, 2023). The cerebellum is characterized by astrocyte heterogeneity, resulting from a complex and still partially unclear process of glial cell proliferation and differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…Because the BONCAT method only labels newly synthesized proteins, there may be challenges with achieving a desired depth of proteome, however, this feature may be an asset for studying event‐related or stimuli‐related changes to the proteome. Recently, BONCAT has been successfully applied to astrocytes as well [163]. The extension of the BONCAT method to label and profile microglia, other brain immune cells and glial subtypes has not been reported thus far.…”
Section: Emerging Isolation‐independent Approaches For Microglial Pro...mentioning
confidence: 99%